Protecting democracy: a parsimonious, dynamic and heuristic model of controlling crimes by the powerful - Ross, Jeffrey Ian (Criminal justice studies, 2017)
Crimes of the powerful (i.e. corporations, elites, organized crime groups, states, white collar criminals, etc.) have numerous devastating effects. That is why, over the centuries, some philosophers and political theorists - and more recently some constitutional experts, and selected social scientists - have proposed and analyzed the best ways to deter, minimize, prevent, regulate, and hereafter control large powerful interests. Not all powerful actors, however, are equally dangerous nor does this threat remain constant. Moreover, not all methods of control work for all entities. In order to better understand this process, one must determine a number of things including: which powerful actor is currently the most dangerous/harmful, where controls do not exist and/or do not function well, and which controls work best and in which particular setting. To achieve this goal, scholarship in diverse fields need to be integrated, with specific reference to the challenges and problems that have arisen and the solutions that have been proposed. To this end, this article develops a parsimonious but dynamic and heuristic model, consisting of a number of interconnected factors, to depict the process of controlling crimes by the powerful.